Archaeological excavations at Beshtasheni Late Bronze Age – Early Iron Age Cemetery (2015-2016 results) - Narimanishvili, Dimitri; Varachkoria, Revaz (ARAMAZD: Armenian Journal of Near Eastern Studies, 2017)
Beshtasheni cemetery is located in South Georgia, in Kvemo Kartli region, north-west from the village Beshtasheni in Tsalka municipality (UTM – Zone: 38T; E: 425700.00, N: 4610700.00.), directly on the road from village Beshtasheni to village Shua Kharaba (formerly known as Saphar-Kharaba), on the right bank of the river Geriak-Chai. Cemetery belongs to ‘Beshtasheni Cyclopean Settlement’, 300 m to the east.